Pengaruh Net Profit Margin (Npm) Dan Total Asset Turnover (Tato) Terhadap Harga Saham Pt Hm Sampoerna Tbk Periode 2014 - 2023 - Slamet Fatchurochim; Lina Nofiana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of Net Profit Margin and Total Asset Turnover on the Stock Price of PT HM Sampoerna Tbk for the period 2014-2023. The method used in this study is a descriptive method with a quantitative approach. The population in this study is the financial statements of PT HM Sampoerna Tbk for the period 2014-2023 and the sample in this study uses a saturated sample, namely using the entire population as a sample. with an error rate of 5%. Data analysis techniques with simple and multiple linear regression. The results of the study show that partially Net Profit Margin (X1) has a positive effect on Stock Price (Y) with a determination coefficient of 52.5% and t count 2.320 > 1.859. Total Asset Turnover (X2) has a positive effect on Stock Price (Y) with a determination coefficient of 72.6% t count 5.078 > 1.859. Net Profit Margin and Total Asset Turnover simultaneously have a coefficient of determination of 84.5% and a calculated F value of 19.120 > 4.35. Based on the results of the calculations that have been carried out, it can be interpreted that H1, H2 and H3 are accepted, this shows that there is evidence of the influence of Net Profit Margin and Total Asset Turnover on Stock Prices both partially and simultaneously.